Communication Strategy for Health Workers in Hospitals in Serving Patients during the COVID-19 Pandemic in Indonesia - Nurdin, Ali; Syaifudin, Mokhamad (Human Sustainability Procedia, 2025)
Health workers are the spearhead in ensuring the community health quality during the COVID-19 (C-19) pandemic. Due to the limitation caused by the C-19 health protocols they must comply with; they need to innovate in their communication strategies to ensure the quality of their services. This study aims to investigate the communication strategies while helping patients during the C-19 pandemic in Indonesia. The study is qualitative employing online questionnaire, consisting few semi-open questions, to collect data. Respondents were invited via social media administered among the health workers. There were 30 respondents who eventually gave their consents to answer the provided questions honestly and frankly. Data analysis is conducted by reducing data, displaying, verifying, then analyze them againts symbolic interactionism, interaction involvement, social information processing theory, and producing research findings. The results of the study indicate that the communication strategy carried out by the health workers while serving patients during the C-19 pandemic; (1) communicating at a distance and by using personal protective equipment (PPE). (2) implementing therapeutic communication to reduce the psychological burden of the patients. (3) adapting online social media-based counseling technique. This health worker communication strategy provides a new direction in the field of health communication during the C-19 pandemic. Health communication requires continuous innovation in facing the unexpected future challenges and events.